Barriers to electronic commerce adoption in small and medium enterprises: a critical literature review - Chitura, T.; Mupemhi, Shepherd; Dube, T.; Bolongkikit, J. (OMICS InternationaL, 2016)
This study is attempting to determine if the barriers reported in early e-commerce researches differ from those found in recent e-commerce studies as well as exploring if the resultant barrier groupings created from e-commerce barriers are dissimilar. To achieve our research’s aim, an extensive literature review was conducted based on what we believe to be representative sample of some of the most cited pieces of research on this topic. The study concludes that though the issues inhibiting SMEs in their uptake of e-commerce are seemingly endless, the reality is that these issues have largely remained the same since the advent of e-commerce in the early 1990’s. The implication of our study is that researchers should stop reinventing the list of e-commerce adoption barriers but instead focus their efforts on how SMEs can overcome these barriers so as to reap the full benefits of the technology.